From Monster to Man: The Transformation of the Vampire and the Gothic Heroine in Dracula and Vampire Diaries - Batubara, Riska (Jetlal, 2024)
Bram Stoker's Dracula and L. J. Smith's Vampire Diaries: The Awakening, separated by a century, both feature the iconic vampire. This study explores how the characterization of the vampire, and its impact on female characters, has transformed within the gothic genre. Utilizing Jungian Archetype theory and textual analysis, this study examines the evolving portrayal of the vampire figure and its connection to the representation of women's horror and madness in the gothic narratives. The analysis reveals a shift in the vampire archetype from Dracula's monstrous and predatory figure to a more romanticized and conflicted one in Vampire Diaries: The Awakening. Additionally, the analysis demonstrates how female characters' experiences of horror and madness transition from fear of the vampire in Dracula to a more complex interplay of fear and desire in Vampire Diaries: The Awakening.